Manajemen Perbankan Syariah, Strategi Dan Praktik Dalam Dunia Bisnis - Delyuzar Syamsi (Program Studi Pendidikan Ekonomi Universitas Pamulang, 2021)
Islamic Banking Management according to Islam which refers to morals, compensation in the form of fulfilling the basic needs of workers, human and spiritual factors, and proximity to subordinates based on ukhuwah Islamiyah (Abu Sin). Sharia Banks as trust institutions that collect and channel third party funds are involved and responsible for improving people's living standards, as mandated by Law Number 21 of 2008 concerning Sharia Banking. Sharia financial institutions have very promising prospects in the fields of banking, insurance, and capital markets. The market potential is very large, both for banking and insurance, although its market share is still below 1%. Understanding and socialization to the public about Islamic banking products and systems in Indonesia is still very limited. This is supported by data obtained by Bank Indonesia, that as of October 2015, Islamic banking was only 3.5-5% of the total national banking market share (the Point, 2015).